Investigation of the role of nutrients for protection against acute kidney injury - Liu, Hui-Hsuan (2017)
Ischaemia reperfusion injury and nephrotoxicity are the common insults of acute kidney injury. Drug induced nephrotoxicity can also lead to an ischaemic phenomenon. The key mediator to both insults is oxidative injury caused by reactive oxygen species, and prolonged injury can result in irreversible kidney fibrosis and chronic kidney disease. This thesis developed a simulated ischaemia reperfusion injury in an in-vitro model to investigate whether amino acid supplementation may facilitate human proximal tubule cell recovery and protect from H2O2 damage following starvation and whether this was mediated by pH. The findings showed that resupply of amino acids at pH 7.5 under H2O2 injury after starvation exacerbated cell death. The mammalian target of rapamycin was also activated in response to amino acids in a concentration dependent manner even if under H2O2 damage, but the link between mammalian target of rapamycin activation and endoplasmic reticulum stress leading to cell death was not yet identified in this thesis. The constant expression of chaperone protein Grp78 may suggest the persistent cellular stress caused by starvation. While amino acids at pH 6.4 failed to activate the mammalian target of rapamycin and potentially reduced protein synthesis, it still exacerbated cell death under H2O2 damage. It also inhibited Grp78 expression, but the link between Grp78 inhibition and cell death was unclear. Moreover, this thesis established an aristolochic acid induced nephrotoxicity in mice and investigated whether another putative nutrient, sodium nitrite, could be renoprotective. However, the therapeutic effects of sodium nitrite remain to be confirmed, as aristolochic acid did not induce any injury in this animal model. Overall, this thesis implicated that the return of circulating amino acids may be detrimental for ischaemia reperfusion injury and that antioxidant therapy may be the priority for acute kidney injury.